Badania marketingowe w przedsiębiorstwie - aspekty poznawcze i efektywnościowe - Michalski, Eugeniusz (Marketing Research in Enterprise - Cognitive and Effectiveness Aspects, 2006)
This paper presents in broad outline ideas and views on enterprise' effectiveness. The effectiveness is considered from the macro- and micro-environments, target markets and a selection marketing research methods. The essential attribute of rational decisions and the strategy of enterprise' development is efficient marketing information system and information derived from original marketing research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 369-376